Exploring Identity and Physical Activity in Substance Use Recovery: An Interpretative Phenomenological Analysis - Coetzer-Liversage, Anthony; Kirkland, Chelsey; Stephens, Peggy C.; Stein, Lynda A. R. (International Journal of Qualitative Research, 2025)
Substance use disorders (SUD) are a significant public health challenge in the United States, with high prevalence among young adults. Physical activity (PA) and identity construction have been found to support SUD recovery and promote a new, substance-free identity. However, more research is needed to understand the links between PA and identity construction. The purpose of this research was to understand the lived experience of how people recovering from a substance use disorder perceive their identity change throughout their self-discovery journey and the role of PA in this journey. Participants were recruited from a local PA group, four 60–90-minute interviews were conducted, and interpretive phenomenological analysis on verbatim transcribed audio files was performed. Three super-ordinate themes were found: 1) Core of Being, 2) Support Connection and Belonging, and 3) Suffering. Findings are consistent with and expand prior research, both within group PA settings and in participants’ journeys.